“Give a man a mask and he’ll tell the truth”: Arnold Schoenberg, David Bowie, and the Mask of Pierrot - Carpenter, Alexander (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2010)
There are striking parallels between Arnold Schoenberg’s treatment of the Pierrot character in 1912 and David Bowie’s adoption of Pierrot as an alter ego in 1980. For both musicians, Pierrot is a necessary mask, and each uses the “insolent clown” in his own way, but in the service of the same delicate negotiations between past and future, and between artifice and truth in art and self. In Schoenberg’s Pierrot Lunaire and Bowie’s song “Ashes to Ashes,” we see and hear the music of the past alongside “a nostalgia for the future”: Pierrot provides the means—the mask—behind which musical reflection, self-examination, and psychological purgation can occur.